1992
DOI: 10.1128/aac.36.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Fleroxacin pharmacokinetics in aqueous and vitreous humors determined by using complete concentration-time data from individual rabbits

Abstract: Although composite data from separate subjects can be used to generate single-subject estimates, intersubject variation precludes rigorous ocular pharmacokinetic analysis. Therefore, a rabbit model in which sequential aqueous and vitreous humor samples were obtained following the administration of the quinolone fleroxacin was developed. Mean data from individual animals were used for pharmacokinetic analysis. Following direct intravitreal or systemic drug administration, sequential paracenteses did not alter p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…Both in vitro and in animal models, fleroxacin's anti-gram-negative-bacterium activity has been shown to be comparable to that of the earlier fluoroquinolones (norfloxacin, pefloxacin, ciprofloxacin, and ofloxacin) (1,2,7,11,13,19,29,36,37,40). In addition, however, studies in endocarditis models, as well as in vitro, have shown that fleroxacin has significant activity against both methicillin-susceptible and -resistant Staphylococcus aureus (1,6,25,28).…”
mentioning
confidence: 97%
“…Both in vitro and in animal models, fleroxacin's anti-gram-negative-bacterium activity has been shown to be comparable to that of the earlier fluoroquinolones (norfloxacin, pefloxacin, ciprofloxacin, and ofloxacin) (1,2,7,11,13,19,29,36,37,40). In addition, however, studies in endocarditis models, as well as in vitro, have shown that fleroxacin has significant activity against both methicillin-susceptible and -resistant Staphylococcus aureus (1,6,25,28).…”
mentioning
confidence: 97%
“…As previously reported, this approach has an advantage of maintaining the integrity of the rabbits , corneas and the anterior chamber volume. When used to study the ocular pharmacokinetics in humans, it yields inaccurate and imprecise estimates because of inter-and intrasubject variations (45). The second technique involves a sequential sampling of the aqueous humor from the same rabbits.…”
Section: Pharmacokinetics Of T-hcl In the Rabbit Aqueous Humormentioning
confidence: 99%
“…By comparing pigmentation, dose mode, and elimination from vitreous humor, the vitreous humor half-life value for singly dosed albino rabbits (3.21 h) was not more rapid than that for singly dosed pigmented rabbits (4.32 h [P > 0.10]) but was more rapid than that for multiply dosed pigmented rabbits (6.05 h [P < 0.05]). The excellent penetration of ofloxacin into uninflamed rabbit eyes in conjunction with the higher levels in blood found in humans and greater activity against coagulase-negative staphylococci suggest that ofloxacin may be preferable to other quinolones for evaluation in the prophylaxis and treatment of bacterial endophthalmitis.We have recently developed and validated an ocular pharmacokinetic animal model which differs from conventional methods that obtain a single sample of vitreous humor from different animals (20,25,26,29). In our model, serial samples are obtained from the vitreous humor after intravenous drug administration.…”
mentioning
confidence: 99%
“…We have recently developed and validated an ocular pharmacokinetic animal model which differs from conventional methods that obtain a single sample of vitreous humor from different animals (20,25,26,29). In our model, serial samples are obtained from the vitreous humor after intravenous drug administration.…”
mentioning
confidence: 99%
See 1 more Smart Citation